The Relationship Between Asian Stock Markets: A Co-Integration Approach - Khan, Noheed; Bilal, Muhammad; Qureshi, Salman Ali; Kashif, Abdul Rauf; Sajid, Abdul Rehman (The journal of contemporary issues in business and government, 2021)
Today’s world capital markets are becoming closely interdependent with each other. This study tests the interdependency and long-term relationship among five Asian financial markets. The results suggest that investors can make their investment portfolio between these financial markets because risk can be diversified in these financial markets. Granger causality test result indicates SSE, HSE and BSE have interdependency on PSE, but CSE has not interdependency on PSE. PSE has not interdependency on SSE and BSE, but PSE has interdependent on HSE and CSE. Granger causality results suggest investor can get the short-run benefit for the international investment portfolio. Cointegration result indicates PSE has a long-term relationship between BSE, HSE, CSE, and SSE. The findings suggest that long-term benefit is limited.